Proceedings of the 35th ACM SIGMOD-SIGACT-SIGAI Symposium on Principles of Database Systems 2016
DOI: 10.1145/2902251.2902287
|View full text |Cite
|
Sign up to set email alerts
|

Towards Tight Bounds for the Streaming Set Cover Problem

Abstract: We consider the classic Set Cover problem in the data stream model. For $n$ elements and $m$ sets ($m\geq n$) we give a $O(1/\delta)$-pass algorithm with a strongly sub-linear $\tilde{O}(mn^{\delta})$ space and logarithmic approximation factor. This yields a significant improvement over the earlier algorithm of Demaine et al. [DIMV14] that uses exponentially larger number of passes. We complement this result by showing that the tradeoff between the number of passes and space exhibited by our algorithm is tight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…A closely related line of work to graph streaming algorithms that have received a significant attention in recent years is on streaming algorithms for submodular optimization and in particular set cover and maximum coverage [9,11,12,26,39,41,50,54,71,88,101,110]. Particularly relevant to our work, [41] uses a reduction from the multi-party tree pointer chasing problem [38] to prove an Ω( log n log log n ) pass lower bound for approximating set cover with m sets and n elements using O(n · poly {log n, log m}) space (this can also be interpreted as a lower bound for the edge-cover problem on hyper-graphs with n vertices and m hyper-edges in the graph streaming model).…”
Section: A Further Related Workmentioning
confidence: 99%
“…A closely related line of work to graph streaming algorithms that have received a significant attention in recent years is on streaming algorithms for submodular optimization and in particular set cover and maximum coverage [9,11,12,26,39,41,50,54,71,88,101,110]. Particularly relevant to our work, [41] uses a reduction from the multi-party tree pointer chasing problem [38] to prove an Ω( log n log log n ) pass lower bound for approximating set cover with m sets and n elements using O(n · poly {log n, log m}) space (this can also be interpreted as a lower bound for the edge-cover problem on hyper-graphs with n vertices and m hyper-edges in the graph streaming model).…”
Section: A Further Related Workmentioning
confidence: 99%
“…We present two algorithms with sub-linear number of queries. First, we show that the streaming algorithm presented in [17] can be adapted so that it returns an O(α)-approximate cover using O(m(n/k) 1/(α−1) + nk) queries, which could be quadratically smaller than mn. Second, we present a simple algorithm which is tailored to the case when the value of k is large.…”
Section: Covermentioning
confidence: 99%
“…The estimation variant of Vertex Cover under the adjacency-list oracle model has been studied in [30,23,29,33]. Set Cover has been also studied in the sub-linear space context, most notably for the streaming model of computation [32,12,7,3,2,5,18,10,17]. In this model, there are algorithms that compute approximate set covers with only multiplicative errors.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly relevant to our work, Demaine et al [23], have shown an α-approximation algorithm that uses O(α) passes over the stream and needs O(mn Θ(1/ log α) ) space. Recently, Har-Peled et al [32] provide a significant improvement over this algorithm: they developed an α-approximation, O(α)-pass streaming algorithm that requires O(mn Θ(1/α) ) space. They further conjectured that the tradeoff between the number of passes and the space in their algorithm is almost tight: this is supported by a lower bound of Ω(mn 1/2p ) space for p-pass streaming algorithms that compute an exact set cover solution [32].…”
Section: Introductionmentioning
confidence: 99%